Search for neutrinoless τ decays: τ→e γ and τ→μ γ - Edwards, K; Bellerive, A; Janicek, R; MacFarlane, D; McLean, K; Patel, P; Sadoff, A; Ammar, R; Baringer, P; Bean, A; Besson, D; Coppage, D; et al. (1997)
A search for the lepton-family-number-violating decays gt;ey and has been performed using II data. Nr> p.virlenrp nf a sipnal ha<; hppn fnnnH anH thp. mrrp.snnnHincr nnnpr limit; are (T-ey)<2.7× 10-6 and B(T->r)<3.0X IQ-6 at 90% C.L. © 1997 The American Physical Society.